Innovating Arabic Language Module Design in Higher Education through a Content-Driven Integrated Model - Meliza Budiarti; Mohammad Taufiq Abdul Ghani (International Journal of Pedagogy and Learning Community (IJPLC), 2026)
This study aims to examine the effectiveness of an e-module developed for the Ilm al-Bayan course at UIN Imam Bonjol Padang through a series of systematic empirical evaluations involving experimental and control groups. The development of the e-module was guided by the ADDIE instructional design model, encompassing five structured stages: needs analysis, design, development, implementation, and evaluation. Prior to hypothesis testing, data normality was assessed using the Kolmogorov–Smirnov and Shapiro–Wilk tests, while data homogeneity was examined using Levene’s test. Inferential statistical analyses included Paired Samples t-Tests to evaluate within-group learning improvements and Independent Samples t-Tests to compare post-test performance between groups. The results indicated that the data from both the experimental and control groups were normally distributed and homogeneous, fulfilling the assumptions required for parametric testing. The Paired Samples t-Test revealed statistically significant improvements in learning outcomes for both groups; however, the experimental group demonstrated a higher mean difference (–7.036, p < 0.05) compared to the control group (–4.673, p < 0.05). The study underscores the potential of e-modules as effective, student-centered pedagogical tools that support interactive learning and contribute to the digital transformation of Arabic language education in higher education.